Searching for you - Hedlund, Jody (Hedlund, Jody. Orphan train., 2018)
"In 1850, Sophie Neumann flees New York with her two young charges after witnessing a crime. Reinhold Weiss has finally purchased his own small farm when an old friend shows up, pleading for help. But how can he help her when mounting debts and past scars still haunt him?"--